THE CONCEPT OF" DISCOURSE " IN THE INTERPRETATION OF FOREIGN LINGUISTS - Madazizova Dilafruz Habibiloevna (Journals Park Publishing, 2022)
In modern linguistics, new directions are entering under the areas of microlinguistics and macrolinguistics. Pragmatics and cognitive linguistics were also among the new directions. At the same time, the issue of "discourse", "discursive analysis" is gaining popularity in Uzbek linguistics as in other world languages. The well-known foreign linguist that the issue of" discourse " is becoming popular and dominant in linguistics V. Z. Demyankov, in his collection" Dominiruyutshie linguisticheskie theory v conke XX ", explains: "one of the dominant theories in linguistics at the end of the 20th century is discourse, the theory of” [2].
Keywords: dominant theories in linguistics, new areas in linguistics.